The Potential of Electronic Media Integrated Islamic Values on Students' Motivation and Creative Thinking Ability - Praptiwi, Ucca Swasti; Yulianto, Agus; Ellianawati, Ellianawati (Unnes Science Education Journal, 2021)
This research is a preliminary study regarding the teacher's description of learning, student learning motivation, students' creative thinking skills, and the need for developing electronic comic learning media based on integrated problem based learning Islamic values at SMPN 3 Watumalang. This research uses a descriptive method. This study's subjects were 44 students of class VIII and teachers of science subjects at SMPN 3 Watumalang. The research was conducted from October to November 2020. The data collection instruments were questionnaires, interview guidelines, and creative thinking skills test questions. The results of interviews with students indicated that the students' intrinsic motivation was still low. The ability to think creatively is still lacking, with a percentage of 42.8%. In the elaboration indicator, most students answered correctly, while in the originality indicator, students were less careful in answering, and only 14.3% of students could answer correctly. Based on the questionnaire analysis results, electronic comic learning media based on problem based learning integrated Islamic values as an alternative media for learning media on vibrations, waves, and sounds in everyday life are needed for development with a percentage of 64%. The use of electronic comics is expected to increase student motivation and creative thinking skills.